Resequencing analysis of five Mendelian genes and the top genes from genome-wide association studies in Parkinson's Disease. Issue 1 (December 2016) - Benitez, Bruno; Davis, Albert; Jin, Sheng; Ibanez, Laura; Ortega-Cubero, Sara; Pastor, Pau; Choi, Jiyoon; Cooper, Breanna; Perlmutter, Joel; Cruchaga, Carlos
Abstract Background Most sequencing studies in Parkinson's disease (PD) have focused on either a particular gene, primarily in familial and early onset PD samples, or on screening single variants in sporadic PD cases. To date, there is no systematic study that sequences the most common PD causing genes with Mendelian inheritance [α-synuclein (SNCA ), leucine-rich repeat kinase 2 (LRRK2), PARKIN, PTEN-induced putative kinase 1 (PINK1 ) andDJ-1 (Daisuke-Junko-1) ] and susceptibility genes [glucocerebrosidase beta acid (GBA ) andmicrotubule-associated protein tau (MAPT )] identified through genome-wide association studies (GWAS) in a European-American case-control sample (n=815). Results Disease-causing variants in the SNCA, LRRK2 andPARK2 genes were found in 2 % of PD patients. TheLRRK2, p.G2019S mutation was found in 0.6 % of sporadic PD and 4.8 % of familial PD cases. Gene-based analysis suggests that additional variants in theLRRK2 gene also contribute to PD risk. TheSNCA duplication was found in 0.8 % of familial PD patients. Novel variants were found in 0.8 % of PD cases and 0.6 % of controls. Heterozygous Gaucher disease-causing mutations in theGBA gene were found in 7.1 % of PD patients. Here, we established that the GBA variant (p.T408M) is associated with PD risk and age at onset. Additionally, gene-based and single-variant analyses demostrated thatGBA gene variants (p.L483P, p.R83C, p.N409S, p.H294Q and p.E365K) increase PD risk. Conclusions Our data suggest that the impact of additional untested coding variants in theGBA andLRRK2 genes is higher than previously estimated. Our data also provide compelling evidence of the existence of additional untested variants in the primary Mendelian and PD GWAS genes that contribute to the genetic etiology of sporadic PD.